(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the design and operating principle of an improved plow for plowing the soil of cotton fields with cotton stalks. It was concluded that when plowing cotton fields with cotton stems, it is advisable to use a disk working tool and a stem bender. The use of disc working bodies as a skimmer helps prevent clogging of the plow with stems and plant debris. In this case, it is considered rational to design a plow with a bender mounted in front of odd bodies, a spherical disk and plow bodies installed in series.